In situ experiments in microgravity and phase-field simulations of the lamellar-to-rod transition during eutectic growth - ŞEREFOĞLU KAYA, MELİS (My University, 2023)
In recent experiments on the solidification of the binary eutectic alloy succinonitrile-(D)camphor carried out on board of the International Space Station (ISS), a transition from rod to lamellar patterns was observed for low growth velocities. The transition was interpreted in terms of a competition between a propagative instability of lamellae and a drift induced by a transverse temperature gradient. Phase-field simulations of a symmetric model alloy support this scenario: for a fixed transverse temperature gradient, the transition from rods to lamellae occurs for a critical composition at fixed velocity, and for a critical velocity at fixed composition. Since the alloy and control parameters used in experiments and simulations are different, our results strongly suggest that this morphological transition is generic for eutectic alloys.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, COMPOSITES; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; General Materials Science; Physical Sciences; Mechanics of Materials; Eutectic alloys; In situ experiments; Microgravity; Modeling; Pattern formation; Solidification; Solidification; Eutectic alloys; In situ experiments; Modeling; Microgravity; Pattern formation